Cargo crimes and its impact in Malaysia perspectives / Harlina Suzana Jaafar … [et al.] - Jaafar, Harlina Suzana; Muhammad, Azlina; Samsuddin, Nur Zulaikha; Tengku Mahmud Shah Al – Haj, Engku Jamaluddin; Mohd Ali, Rosena (Malaysia Institute of Transport (MITRANS), 2013)
Cargo crime has become a discordant issue in this troublesome and challenging era of international business and crimes related issues. Cargo crime includes hijacking, warehouse thievery, lost in transit and many more. Cargo theft on the highway can be defined as any theft with shipment committed during its road transportation or within a warehouse or premises. One of the famous cargo crime or theft is hijacking. Hijacking usually happened on the road or in the parking area during transhipment process. Vehicle hijacking of trucks with freight is one of the guises robberies, which made the hijacking, is under the same crime as robbery. As the globe turning in a very fast way, currently Logistics Company had become important to accelerate the business process and nations economy. The objectives of this report are to assure the present scenario of cargo crime in Malaysia and evaluate the level of threat towards the logistics industry, to identify the factors that attracts cargo crime to occur and finally to provide recommendation on important the number of cargo crime incidents. The methods used in this report are towards data analysis and also interview with several key personal candidates in creating this report a visible and knowledgeable analysis.